Thy-1 in Integrin Mediated Mechanotransduction - Hu, Ping; Barker, Thomas H. (Frontiers in Cell and Developmental Biology, 2019)
The glycosylphosphatidylinositol (GPI) anchored glycoprotein Thy-1 has been prevalently expressed on the surface of various cell types. The biological function of Thy-1 ranges from T cell activation, cell adhesion, neurite growth, differentiation, metastasis and fibrogenesis and has been extensively reviewed elsewhere. However, current discoveries implicate Thy-1 also functions as a key mechanotransduction mediator. In this review, we will be focusing on the role of Thy-1 in translating extracellular mechanic cues into intracellular biological cascades. The mechanotransduction capability of Thy-1 relies on trans and cis interaction between Thy-1 and RGD-binding integrins; and will be discussed in depth in the review.